Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.7453/gahmj.2015.048
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Chronic Pain: A Human Systems Approach—Results from a Massive Open Online Course

Abstract: Chronic pain conditions are the top reason patients seek care, the most common reason for disability and addiction, and the biggest driver of healthcare costs; their treatment costs more than cancer, heart disease, dementia, and diabetes care. The personal impact in terms of suffering, disability, depression, suicide, and other problems is incalculable. There has been much effort to prevent many medical and dental conditions, but little effort has been directed toward preventing chronic pain. To address this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 40 publications
0
42
0
2
Order By: Relevance
“…The most common measure was participant satisfaction with twelve studies reporting overwhelmingly positive experiences of participation in MOOCs. However one study [30] reported the participants were neutral in their assessment of satisfaction (Likert Scale score of 0.0 (95% CI − 1.1 to 1.2), and another [21] reported that only 56% of learners were satisfied with the quality of the course discussion forums. One study [39] provided strong agreement from participants for the helpfulness of a virtual patient experience.…”
Section: Learner Experience (Attitudes Of Health Professionals Towardmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common measure was participant satisfaction with twelve studies reporting overwhelmingly positive experiences of participation in MOOCs. However one study [30] reported the participants were neutral in their assessment of satisfaction (Likert Scale score of 0.0 (95% CI − 1.1 to 1.2), and another [21] reported that only 56% of learners were satisfied with the quality of the course discussion forums. One study [39] provided strong agreement from participants for the helpfulness of a virtual patient experience.…”
Section: Learner Experience (Attitudes Of Health Professionals Towardmentioning
confidence: 99%
“…One study [39] provided strong agreement from participants for the helpfulness of a virtual patient experience. One study [21] included qualitative comments from participants, reporting that the course helped with self-discovery, and expanded their view of the world. Whereas another [25] reported that they found the course provided an opportunity engage with other health professionals and health professional students from around the globe.…”
Section: Learner Experience (Attitudes Of Health Professionals Towardmentioning
confidence: 99%
“…In addition, the stigma and discomfort of caring for patients with chronic pain has been accentuated by the current opioid crisis . Based on the work of James Fricton at the University of Minnesota, we implemented a 2‐hour interactive educational session using a whole‐person approach to the treatment of chronic pain that considered all factors influencing a patient's perception and experience of pain . The most surprising discussion of the session focused on the stigma associated with chronic non‐malignant pain.…”
mentioning
confidence: 99%
“…In terms of prevalence, the World Health Organization recognizes CP as a public health problem worldwide [10] (32% in low income countries and 30% in high income countries) [11,12]. In the US alone, 120 million adults are reported to be suffering from CP [13].…”
mentioning
confidence: 99%
“…In terms of prevalence, the World Health Organization recognizes CP as a public health problem worldwide [10] (32% in low income countries and 30% in high income countries) [11,12]. In the US alone, 120 million adults are reported to be suffering from CP [13].Related costs have exceeded diabetes, cancer and heart disease in US [14] and CP is also related to substance abuse; 12 million (12 year or older) reported non-medical use of pain medication and overdose related deaths are rising every year [15].A particularly common form of CP is musculoskeletal chronic pain, which affects one in ten adults globally; 28.1% of the CP population has a musculoskeletal form.Musculoskeletal CP is a leading cause of disability, with 28% of people with chronic back pain reporting limited movement due to the condition [16]. Having said this, it is well understood that successful management in musculoskeletal CP is achievable with regular and sustained physical activity [10].…”
mentioning
confidence: 99%